Virtual vs Real Lab: A Comparative Study on the Effectiveness of Laboratory-Based Physics Learning on Students’ Critical Thinking Skills - Sabrina, Nadya Mazayu Nur; Jatmiko, Budi; Nisa', Khoirun (Universitas Negeri Surabaya, 2025)
Objective: This study aims to compare the effectiveness of guided inquiry learning using worksheets (SW) based on Virtual Lab (PhET) and Real Lab in enhancing students’ critical thinking skills in physics learning. Method: This study employed a quasi-experimental method with a non-equivalent pretest–posttest design involving two experimental classes in a public senior high school in Surabaya during the even semester of the 2024/2025 academic year. A saturated sampling technique was applied, in which all 11th-grade science students were included as the research sample. The first class used SW integrated with PhET simulations, while the second class used SW based on real laboratory activities. The instrument used was a critical thinking skills test developed based on Facione’s five indicators, and the data were analyzed using gain score analysis, paired sample testing, independent sample testing, and effect size analysis. Results: The findings showed that both experimental classes experienced significant improvement in students’ critical thinking skills after the implementation of guided inquiry learning, with no significant difference found between the two groups, indicating that both approaches are comparably effective. Novelty: The novelty of this study lies in its direct comparative design, demonstrating that both virtual and real laboratory modalities can equally support the development of critical thinking skills and provide flexible alternatives for physics learning in schools with different laboratory facilities.